Critical assessment of secondary findings in genes linked to primary arrhythmia syndromes. Issue 5 (18th February 2020) - Diebold, Isabel; Schön, Ulrike; Scharf, Florentine; Benet‐Pagès, Anna; Laner, Andreas; Holinski‐Feder, Elke; Abicht, Angela
Abstract: As comprehensive sequencing technologies gain widespread use, questions about so‐called secondary findings (SF) require urgent consideration. The American College of Medical Genetics and Genomics has recommended to report SF in 59 genes (ACMG SF v2.0) including four actionable genes associated with inherited primary arrhythmia syndromes (IPAS) such as catecholaminergic polymorphic ventricular tachycardia, long QT syndrome, and Brugada syndrome. Databases provide conflicting results for the purpose of identifying pathogenic variants in SF associated with IPAS at a level of sufficient evidence for clinical return. As IPAS account for a significant proportion of sudden cardiac deaths (SCD) in young and apparently healthy individuals, variant interpretation has a great impact on diagnosis and prevention of disease. Of 6381 individuals, 0.4% carry pathogenic variants in one of the four actionable genes related to IPAS: RYR2, KCNQ1, KCNH2, and SCN5A. Comparison of the databases ClinVar, Leiden Open‐source Variant Database, and Human Gene Mutation Database showed impactful differences (0.2% to 1.3%) in variant interpretation improvable by expert‐curation depending on database and classification system used. These data further highlight the need for international consensus regarding the variant interpretation, and subsequently management of SF in particular with regard to treatable arrhythmic disorders with increased risk of SCD. Abstract : We critically assessed secondary findings (SF) in actionable genes (RYR2, KCNQ1, KCNH2, and SCN5A) linked to inherited primary arrhythmia syndromes. Comparison of the databases showed impactful differences in variant interpretation. The study highlights the need of international consensus regarding the variant interpretation, and subsequently management of SF in particular with regard to treatable arrhythmia disorders with increased risk of sudden cardiac death.